"God is My First Aid Kit": The Negotiation of Health and Illness among Christian Scientists. Issue 3 (16th August 2018) - Steckler, Rebecca A.; Bartkowski, John P.
Abstract: Christian Scientists' rejection of conventional medical practices has generated considerable controversy. Using insights from theories of subcultural identity and cultural repertoires, we analyze elite discourse and adherent narratives from 20 Christian Scientists to examine how this nonmedicalized religion engages the challenges posed by the highly medicalized character of American society. The writings of Christian Science founder Mary Baker Eddy primarily exhibit a critical posture toward conventional medicine, although conciliatory language is also evident in these same works. These discursive nuances provide Christian Science adherents with latitude in negotiating health and illness in their everyday lives. Interview data reveal that negotiated health practices are particularly evident in three domains: using prayer as a means of seeking divine guidance, developing metaphysical competency as a healer, and weighing options based on legal mandates for seeking medical treatment. We conclude by specifying the implications of our findings and identifying directions for future research.